The Role Of Innovative Technologies In Preventing Youth Alienation From Work (Czech Journal of Multidisciplinary Innovations, 2022)
The article provides a philosophical analysis of the prevention of strategic directions of labor alienation of youth. In modern society, alienation from work is becoming dangerous. The most urgent task is to involve modern youth in useful work, directing it in the right direction. The role of spiritual factors in preventing labor alienation is also increasing. After all, insufficient attention to spiritual factors in the organization of labor leads a person to spiritual poverty.